Desenvolvimento de competências em empresas gazelas: a perspectiva dos líderes - Manteiga, Sandro Magalhães (2022)
Gazelles are high-growth young companies that make a major contribution to the creation of formal jobs. Despite this importance, most studies on gazelles are population-based and do not address the high growth process. This study focused on understanding how gazelle leaders develop organizational competencies for growth, from the integration of EffectuationCausation and Dynamic Capabilities perspectives. Twenty-seven interviews and four case studies were carried out, which resulted in five propositions integrated into a framework. This article contributes to the literature on entrepreneurship by explaining the iterative and incremental process of the development of competencies and how it is influenced by strategic and cultural factors, by the exponentially growing size of gazelles and by antecedents linked to leadership itself. Implications and management practices for entrepreneurs and researchers are discussed.